Using artificial intelligence in the fight against spam. Issue 7 (July 2019) - Oetjen, Jan
Abstract : More than 40 years ago, on 3 May 1978, a computer vendor in the US sent the first spam email in history. It was sent by marketing manager Gary Thuerk to a list of 320 people who were active at that time on Arpanet, a predecessor of today's Internet, and was to invite them to the launch of a new computer in Los Angeles and San Mateo.